PENGELOLAAN SUPERVISI KLINIS SEKOLAH STANDAR NASIONAL PANDEAN 1 KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Rahayu, Dwi (2011)
This research purposes are describe character (1) teacher activity which monitored by Pandean 1 National Standard Elementary School Ngemplak subdistrict Boyolali district. (2) supervisor activity of Pandean 1 National Standard Elementary School Ngemplak subdistrict Boyolali district. (3) supervisor and teacher relation teamwork in Pandean 1 National Standard Elementary School Ngemplak Subdistrict Boyolali district. This research is a qualitative research. Research location is in Pandean 1 National Standard Elementary School Ngemplak subdistrict Boyolali district. Data source uses events/activities and arcipt and document. Collecting data technique uses observation, depth interview, documentation. Data analysis mode uses managed data analysis method in site for description. Data legality test uses data credibility or trustness to research result data with triangulation. Research results are (1) RPP (lesson plan) arrangement activity includes: basic competency formulation and indicator, planning and material organization, class management plan, lesson medium source using plan, assessment plan, and lesson plan physic form. When supervision of class visit done, teacher explains about many teacher's problems in arranging lesson execution plan arrangement, lesson execution, or lesson evaluation. (2) supervisor does observation to teacher's learning execution to observe directly how teacher executes learning and notes about learning plan, including: learning purposes formula clarity, material choosing, material organization, medium/ source choosing, planning scenario clarity, instrument completeness. Supervisor activity in observation focus on supervision flexibility, do not disturb learning process, do not assessing, noting and recording anything in learning process according to previous discussion, and deciding observation execution technique. (3) supervisor and teacher teamwork relation in learning plan by communicating learning execution plan with teacher in friend and common situation, both in class (in door) or out class (outdoor) in objective discussion. Supervisor and teacher teamwork relation purposes to help teacher fixing and improving learning execution plan quality and help to identify and analyze raising problem in learning execution plan arrangement based on teacher prepared data and discussion results.